Uso da iluminação por leds na embriogênese somática e seu efeito na aclimatação de cana-de-açúcar - FERREIRA, Lais Tomaz (2015)
The light source used in in vitro culture interferes in the morphogenesis and contributes to the quality of the obtained plantlets. Therefore, this study aimed to evaluate the use of LEDs in the induction of somatic embryogenesis, in the micropropagation and as this reflected in the acclimatization of sugarcane (RB98710). For ES induction immature leaf segments were inoculated on MS medium supplemented with two combinations of 2,4-D and BAP, forming treatments: C1- 13.6 μM of 2,4-D + 2.2 μM BAP and C2- 9 μM of 2,4-D + 1.1 μM BAP. For plant regeneration was used medium devoid of growth regulators. For multiplication used the concentrations of 4,44 μM BAP and 4,65 μM KIN during six consecutive subcultures; and for rooting, used 5.37 μM ANA. The cultures remained under fluorescent lights - FL (50 μmol m-²s-¹) or LEDs (80 μmol m-²s-¹), and after rooting plants were acclimatized. The medium C2 under LED lighting provided a higher percentage of responsive explants, however, the largest number of plants was obtained under C1 under FL lighting, averaging 26.75 plants/explant. Histological analysis revealed that there was embryo formation directly and indirectly from the explant. Plants grown under LEDs showed a higher proliferation rate compared to FL, averaging 5.06 and 4.20, respectively. After acclimatization plants from LED lighting showed 96% survival while they were under FL had 75%. The loss of water in leaves was about 10% lower for plants in LEDs. With regard to biometric parameters and carotenoids content, the best results were observed in plants derived from in vitro culture under LEDs. The H2O2 content before and during the acclimatization was higher in plants under LED still MDA content not differentiate between sources of light. The antioxidant enzymes were effective in combating oxidative stress in both lighting systems. Thus, it can be inferred that plants of sugarcane variety RB98710 have better rate of multiplication and development in vitro and ex vitro when cultured under the LEDs.